2004
DOI: 10.1016/j.ymthe.2004.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Exon Skipping in Transgenic hDMD Mice: A Model for Direct Preclinical Screening of Human-Specific Antisense Oligonucleotides

Abstract: The therapeutic potential of frame-restoring exon skipping by antisense oligonucleotides (AONs) has recently been demonstrated in cultured muscle cells from a series of Duchenne muscular dystrophy (DMD) patients. To facilitate clinical application, in vivo studies in animal models are required to develop safe and efficient AON-delivery methods. However, since exon skipping is a sequence-specific therapy, it is desirable to target the human DMD gene directly. We therefore set up human sequence-specific exon ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 32 publications
1
83
3
1
Order By: Relevance
“…This variability has been demonstrated in 2OMeAO-induced skipping of a variety of human exons in tissue culture and in a mouse carrying the human genomic dystrophin gene. But these studies have also found that a large proportion of exons are readily skipped by the use of appropriate AO sequences (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…This variability has been demonstrated in 2OMeAO-induced skipping of a variety of human exons in tissue culture and in a mouse carrying the human genomic dystrophin gene. But these studies have also found that a large proportion of exons are readily skipped by the use of appropriate AO sequences (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…As a proof of principle, the AOs were also tested on muscle explants from DMD patients to study their effect in an ex vivo structure, as such explants have been described as a putative model in which to test gene therapy models McClorey et al, 2006a). These experiments were complemented by the intramuscular administration of PMO versions of the two most promising sequences into the gastrocnemius muscle of a mouse model transgenic for the entire human dystrophin locus (Bremmer-Bout et al, 2004). All these approaches suggested that one of the AOs (AO B30, ϩ66ϩ95) more robustly induced exon skipping, and this sequence has now been chosen for the phase I/IIa trial which is underway in the United Kingdom.…”
Section: Introduction Dmentioning
confidence: 99%
“…Subsequently, the same approach was successfully used in the mdx mouse model by intramuscular or i.v. delivery of AONs (11)(12)(13)(14). The antisense approach resulted in very efficient rescue of the dystrophin protein even though the effect of AONs is limited in time, thus requiring multiple administrations.…”
mentioning
confidence: 99%